Windows Server 2003 security : a technical reference - Bragg, Roberta (Addison-Wesley, 2005)
"Once again, Roberta Bragg proves why she is a leading authority in the security field! It's clear that Roberta has had a great deal of experience in real-world security design and implementation. I'm grateful that this book provides clarity on what is often a baffling subject!" James I. Conrad, MCSE 2003, Server+, Certified Ethical Hacker James@accusource.net "Full of relevant and insightful information. Certain to be a staple reference book for anyone dealing with Windows Server 2003 security. Roberta Bragg's Windows Server 2003 Security is a MUST read for anyone administering Windows Server 2003." Philip Cox, Consultant, SystemExperts Corporation phil.cox@systemexperts.com "Few people in the security world understand and appreciate every aspect of network security like Roberta Bragg. She is as formidable a security mind as I have ever met, and this is augmented by her ability to communicate the concepts clearly, concisely, and with a rapier wit. I have enjoyed working with Roberta more than I have on any of the other 20 some odd books to which I have contributed. She is a giant in the field of network security." Bob Reinsch bob.reinsch@fosstraining.com " Windows Server 2003 Security explains why you should do things and then tells you how to do it! It is a comprehensive guide to Windows security that provides the information you need to secure your systems. Read it and apply the information." Richard Siddaway, MCSE rsiddaw@hotmail.com "Ms. Bragg's latest book is both easy to read and technically accurate. It will be a valuable resource for network administrators and anyone else dealing with Windows Server 2003 security." Michael VonTungeln, MCSE, CTT mvontung@yahoo.com "I subscribe to a number of newsletters that Roberta Bragg writes and I have 'always' found her writing to be perfectly focused on issues I 'need' to know in my workplace when dealing with my users. Her concise writing style and simple solutions bring me back to her columns time after time. When I heard she had written a guide on Windows 2003 security, I 'had' to have it. Following her guidance on deployment, her advice on avoiding common pitfalls, and her easy to follow guidelines on how to lock down my network and user environments (those darned users!) has me (and my clients) much more comfortable with our Win2k3 Server deployments. From AD to GPO's to EFS, this book covers it all." Robert Laposta, MCP, MCSA, MCSE, Io Network Services, Sierra Vista AZrob.laposta@cox.net "R...